2015
DOI: 10.4018/978-1-4666-8170-5.ch013
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the Acceptance of Innovative Technologies Used in Learning Opportunities

Abstract: In this chapter, the author presents a theoretical framework to better understand how individuals adapt to innovative technology used to support learning opportunities. This chapter begins with an overview of literature concerning technology acceptance, specifically centered on the seminal work of Venkatesh, Morris, Davis, and Davis (2003). This is followed by a discussion of three theoretical perspectives change that include Lewin's (1997, 1952) change model, Schein's (1996) adaptation of Lewin's model as it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, for any of this to be successful, organizations of the future must ensure that steps are taken to facilitate the adoption of innovation (Rogers, 2003 ) and technology (McGurn & Prevou, 2012 ; Pavera, Walkera, & Hunga, 2014 ). Research (Davis, F. D., 1989 ; Lee, Kozar, & Larsen, 2003 ; Moats, 2015 ; Venkatesh, Morris, Davis, & Davis, 2003 ; Yen, Wu, Cheng, & Huang, 2010 ; Yousafzai, Foxall, & Pallister, 2007 ) has shown that technology is more likely to be accepted by users when several criteria are met. First, one must understand how the technology will help him or her perform the job better.…”
Section: A Way Forwardmentioning
confidence: 99%
See 3 more Smart Citations
“…However, for any of this to be successful, organizations of the future must ensure that steps are taken to facilitate the adoption of innovation (Rogers, 2003 ) and technology (McGurn & Prevou, 2012 ; Pavera, Walkera, & Hunga, 2014 ). Research (Davis, F. D., 1989 ; Lee, Kozar, & Larsen, 2003 ; Moats, 2015 ; Venkatesh, Morris, Davis, & Davis, 2003 ; Yen, Wu, Cheng, & Huang, 2010 ; Yousafzai, Foxall, & Pallister, 2007 ) has shown that technology is more likely to be accepted by users when several criteria are met. First, one must understand how the technology will help him or her perform the job better.…”
Section: A Way Forwardmentioning
confidence: 99%
“…This is especially important when the opinions are from those who are important to the user (e.g., the boss, a trusted colleague, etc.) (Moats, 2015 ; Venkatesh et al, 2003 ). A final, but important criterion is that the user believes that the organization can support the implementation and the sustained use of the technology (Venkatesh et al, 2003 ).…”
Section: A Way Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…However, incorporating tablet technology into students' learning also increases the complexity of, and creates additional challenges and anxieties for managing classroom settings. These challenges and anxieties regarding teachers' adoption might result in rejection of the technology (Moats, 2015).…”
Section: Activities For Integrationmentioning
confidence: 99%